Studies of ferroelectric and magnetic phase transitions in Pb(Fe0.5Nb0.5)1-xCexO3 multiferroic ceramics. (25th October 2020) - Raevskaya, S. I.; Titov, V. V.; Raevski, I. P.; Kubrin, S. P.; Chou, C.-C.; Shevtsova, S. I.; Malitskaya, M. A.; Zakharchenko, I. N.
Abstract: Multiferroic Pb(Fe0.5 Nb0.5 )1-x Cex O3 (x = 0.025, 0.05, 0.075, 0.10) ceramic compositions were prepared by solid state synthesis and usual sintering. XRD studies have shown a formation of the perovskite structure in all the compositions studied. However a small amount of pyrochlore phase was detected in Ce-doped compositions with x ≥ 0.075. Scanning electron microscopy studies and elemental analysis have shown that at the boundaries of the large grains of nearly pure PbFe0.5 Nb0.5 O3 there exist a lot of small submicron grains enriched by Ce. Concentration dependencies of the unit-cell parameter and temperatures of ferroelectric and magnetic phase transitions also imply that solubility of Ce in PFN does not exceed ≈ 2 at.%.